2009
DOI: 10.1210/jc.2008-2371
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Variants in the Hepatocyte Nuclear Factor-1α Gene in South Indian Patients with Maturity Onset Diabetes of Young

Abstract: This study suggests that mutations in the HNF1A gene comprise about 9% of clinically diagnosed MODY subjects in southern India and a novel Arg263His mutation cosegregates with MODY in one family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 27 publications
3
40
1
1
Order By: Relevance
“…(50) A study of HNF1A in Indian suspected MODY patients found 9% of cases have HNF1A mutations. (51) Similar studies for HNF4A have shown the prevalence to be 3.4% of suspected MODY cases. (52) However, when 49 children and adolescents from a study in Chennai, India with hyperglycemia were sequenced for GCK mutations, none were discovered, despite other case reports of GCK -MODY in Indian patients.…”
Section: Mody Epidemiology Studiesmentioning
confidence: 83%
“…(50) A study of HNF1A in Indian suspected MODY patients found 9% of cases have HNF1A mutations. (51) Similar studies for HNF4A have shown the prevalence to be 3.4% of suspected MODY cases. (52) However, when 49 children and adolescents from a study in Chennai, India with hyperglycemia were sequenced for GCK mutations, none were discovered, despite other case reports of GCK -MODY in Indian patients.…”
Section: Mody Epidemiology Studiesmentioning
confidence: 83%
“…they are non-diabetic (up to 2 generations). The study done in the Eastern Indian population as published Indian studies on MODY is quite sparse [14].…”
Section: Discussionmentioning
confidence: 99%
“…Among 96 young onset diabetic patients screened for HNF1A gene mutation, we identified nine mutations (9.6%). A novel HNF1A gene mutation Arg263His co-segregated with diabetes in a family of 30 individuals; it was not seen in non-diabetic members in the family, thus providing evidence for the mutation to be involved in MODY 78 . This mutation was further evaluated for pathogenicity using functional genomic assays which demonstrated that the mutant acts as dominant negative suppressor and causes MODY 3 in the affected family, due to reduced HNF1A transactivation potential, DNA binding to HNF1A targets and improper nuclear translocation 79 .…”
Section: Studies On Mody In Indiamentioning
confidence: 95%